2000
DOI: 10.1016/s0035-9203(00)90284-0
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic concentrations of tumour necrosis factor-α, interleukin-6 and interleukin-8 in bacterial osteomyelitis

Abstract: Osteomyelitis is a major cause of morbidity worldwide but there are few data investigating pathogenesis of infection and no investigations into local secretion of proinflammatory cytokines in patients. Tumour necrosis factor-alpha (TNF), interleukin (IL)-6 and IL-8 concentrations were measured in pus of infected bone from 30 Zambian patients with chronic osteomyelitis (principally caused by Staphylococcus aureus), in plasma, and after lipopolysaccharide stimulation of whole-blood leucocytes. Patients had reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…8 We confirm the elevated expression of mRNA encoding the key proinflammatory cytokine, IL-6, in bacterially infected bone consistent with earlier studies in murine bone tissue 15 and with our previous studies using isolated osteoblasts. 4 Importantly, in the present study we provide the first in vivo evidence for osteoblasts as a significant source of such inflammatory mediator production in response to bacterial challenge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8 We confirm the elevated expression of mRNA encoding the key proinflammatory cytokine, IL-6, in bacterially infected bone consistent with earlier studies in murine bone tissue 15 and with our previous studies using isolated osteoblasts. 4 Importantly, in the present study we provide the first in vivo evidence for osteoblasts as a significant source of such inflammatory mediator production in response to bacterial challenge.…”
Section: Discussionsupporting
confidence: 91%
“…18 However, the generation of proinflammatory cytokines and chemokines is thought to be pivotal in the recruitment and activation of infiltrating immune cells and in the net balance between bone resorption and formation. Recent studies have demonstrated the local production of key inflammatory cytokines, such as IL-6, at sites of bacterial infection in human S. aureus-associated osteomyelitis 15 and a murine model. 9 While it is likely that infiltrating immune cells, such as monocytes/macrophages, are an important source of such molecules, our recent work has demonstrated the surprising ability of osteoblasts to produce significant amounts of an array of soluble immune mediators following in vitro exposure to clinically relevant bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, inflammatory cytokines induce osteomyelitisassociated regulation of osteoclast activity and bone destruction directly (14)(15)(16)(17) and/or indirectly through stimulation of the release of key bone-remodeling factors (18). On the other hand, the anti-inflammatory cytokine IL-4, acting by downregulating IL-1 and Th1-type cytokine production (19,20), was described to be involved in the restoration of damaged bone tissue in osteomyelitis (21).…”
mentioning
confidence: 99%
“…Involvement of human monocyte cells in this process has been well-described. When presented with Staphylococcus aureus cells or bacterial cell wall components such as peptidoglycan (PepG) or lipopolysaccharide (LPS), monocytes secrete large amounts of interleukin 1-beta (IL-1beta), IL-6, IL-8, tumour necrosis factor alpha (TNFalpha) and macrophage inflammatory protein 1-alpha (MIP-1alpha) (Fullilove et al, 2000;Klosterhalfen et al, 1996;Wang et al, 2000). This has been confirmed in an in vivo animal model demonstrating up-regulation of cytokines following intravenous infusion of PepG and LPS (Ruud et al, 2007).…”
Section: Inflammatory Response To Infectionmentioning
confidence: 99%